An Important Strategy to Improve Adolescent Health Literacy: COVID-19 Modules in High School in Indonesia - Nurina Hasanatuludhhiyah; Visuddho Visuddho; Abdul Khairul Rizki Purba; Annette d' Arqom; Ancah Caesarina Novi Marchianti (Korean Society for Preventive Medicine, 2023)
Objectives During the second coronavirus disease 2019 (COVID-19) surge, cases increased sharply due to low awareness and compliance with measures to limit disease spread. Health literacy (HL) is an important component of public health initiatives, and schools are potential sources of health education to increase HL via the presentation of COVID-19 educational modules. Methods This cross-sectional study involved an online questionnaire administered to students from 5 high schools in Surabaya and Sidoarjo, Indonesia, 6-7 weeks after the start of government-issued directives restricting public gatherings. We collected data on each respondent's age, gender, parental education, and socioeconomic variables. HL was determined by the Health Literacy Measure for Adolescents. We additionally measured their attitudes and behaviors related to preventing the spread of COVID-19. The students were asked if they watched the COVID-19 module at school, their feelings about vaccination, and preferred online sources of COVID-19-related information. Results Most of the 432 respondents had viewed COVID-19 modules at school. Module exposure was associated with significantly higher total and domain-specific HL and more positive attitudes toward government-issued COVID-19 restrictions on travel and public gatherings (p<0.05). However, behaviors to prevent COVID-19 spread and vaccine acceptance were not associated with module exposure. Most students chose social media as their source of COVID-19-related information. Conclusions Schools can provide information to increase adolescents' HL and the public's support for health initiatives to prevent or limit the spread of COVID-19.